Supported vs Substituted: The Urgency of Regulating Limited Guardianship for Individuals with Psychosocial Disabilities in Islamic Inheritance - Franola, Frida Azmil; Rohmah, Siti; Sari, Shinta Puspita (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The authority to manage inheritance assets in Islamic inheritance law by guardians of individuals with psychosocial disabilities highlights the urgency of limiting such authority to preserve maqashid sharia, particularly the protection of individual property and life. Current regulations in Indonesia regarding guardianship remain discriminatory and do not explicitly restrict the powers of guardians, leading to potential abuse. This study aims to analyze the urgency of limited guardianship regulation from an Islamic legal perspective and to formulate a legal framework that aligns with the supported decision-making paradigm. The methodology employed is normative research using legal, conceptual, and comparative approaches against regulations in Aceh Besar, Pakistan, and England. The findings indicate that the current guardianship regulations in Indonesia tend to adopt a substituted decision-making paradigm, granting full authority to guardians without involving individuals with disabilities in decision-making processes. This paradigm contradicts the Convention on the Rights of Persons with Disabilities (CRPD) ratified by Indonesia. To address this legal gap, regulatory reform is necessary, including restricting guardian authority, implementing strict oversight, and establishing criminal penalties for guardians who violate these provisions. This study recommends adopting a more inclusive supported decision-making paradigm where guardians act as decision supporters without replacing the legal rights of individuals with disabilities. Such reform aligns with the principles of social justice in Pancasila and maqashid sharia, creating a more inclusive legal system that protects the rights of individuals with psychosocial disabilities while preventing discrimination and abuse of power in managing inheritance assets.